Capital Market Reaction to the Announcement of BI Rate Cut on LQ45 Index Banking Stocks - Khairani, Lutfia; Aristantia , Selvia Eka (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to determine the differences in Abnormal Return and Trading Volume Activity before and after the announcement of the BI Rate reduction in LQ-45 index banking companies. This study uses the event study method. This study uses secondary data, which is data obtained directly through intermediary media and is data obtained and recorded by another party or a second party. The data consists of documents and information in the form of daily stock prices and trading volumes that can be accessed through the official website of the Indonesia Stock Exchange and through yahoo.finance.com. The results of the study show: (1.) There is a significant difference in abnormal returns before and after the announcement of the BI Rate reduction. (2) There is a significant difference in trading volume activity before and after the announcement of the BI Rate reduction.